Improving the hospital or immunizing its organization? Patient and public involvement at the service of quality - Voz, Bernard; Pétré, Benoît; Orianne, Jean-François (Frontiers in Sociology, 2024)
IntroductionThere is a pressing need for the hospitals to improve their quality and become more patient-centered. Over the last decade, several approaches were implemented to meet this demand, such as hospital accreditation or patient surveys. Many studies have addressed the patient involvement systems from the viewpoint of the factors that drive them or the achieved performance. In this study, we examined the patient involvement from the viewpoint of its function and operation rather than its performance. Following Luhmann, we reconsidered quality to be related to the absorption of uncertainty rather than improvement or innovation. The adaptation of an organization to involve patient participation can be regarded as contributing to the immune function of the organizational system.MethodsThree case studies addressing patient and family advisory councils in general hospitals were conducted in Belgium. Qualitative empirical material is retrieved from observation, documentation, and interviews.ResultsOur findings suggest that the immune function of the hospital organization operates in four main phases. First, we assess how the communicative process indicates the relevant difference that needs to be addressed. Role differentiation occurs through the depoliticization and depersonalization of criticism. Second, given the impossible realization of first-order observation of the environment, our material shows how second-order observation is organized through a dual representation. Third, we unveil how the environmental representation requires a specific organizational socialization to overcome the representation paradox. Finally, we analyze how the whole described process must fulfil the preparation of a repertoire of responses to the irritations of its environment.DiscussionThe analysis revealed that patient and family advisory councils complete a crucial immune function for organizations, far beyond the simple discussion of the “nuts and bolts” of organizational structure. These findings permit to discuss implications of the notions of participation and quality regarding to identity work of stakeholders, open organization, and change management.